Carbon neutrality cognition, environmental value, and consumption preference of low-carbon products - Li, Baoku; Nan, Yafeng; Yao, Ruoxi (Frontiers in Environmental Science, 2022)
It is now the mainstream scientific consensus that carbon emissions cause global climate change. Achieving the goal of China’s carbon neutrality is essential for environmental protection and economic sustainable development all over the world. In the above context, this paper aims to explore the carbon neutrality cognition, environmental value, and consumption preference of low-carbon products from the perspective of consumption end. Thus, we build and check a new conceptual model of consumers’ carbon neutrality cognition and the consumption preference of low-carbon products. Method of TF-IDF algorithm in Machine Learning is used to confirm the dimensions of carbon neutrality cognition based on text data collected from an academic database CNKI. Then, we deal with data from a social investigation (N = 405) to test hypotheses and model using methods of Bootstrap and Independent-sample t test. The results present that altruistic (β = 0.168, 95% CI: [-0.54514, 0.8819],) and egoistic values (β = -0.066, 95% CI: [-0.6361, 0.6772]) mediate the impact of carbon neutrality cognition on the consumption of low-carbon products, but egoistic value does not (β = -0.066, 95% CI: [-0.6361, 0.6772]). Additionally, based on the characteristics of current Chinese consumers and the market, we argue two boundary factors: face consciousness and carbon footprint label. The moderation of face consciousness (M high = 5.395 vs. M low = 3.312) and carbon footprint label (M with =6.394 vs. M without = 5.432), are revealed. The empirical results support our conceptual model, and our findings recommend policymakers and enterprises insight into people’s carbon neutrality cognition to make more appropriate policies and sustainable development strategies.